How does dispositional mindfulness foster prosocial behavior? A cross-cultural study of empathy’s mediating role and cultural moderation - Li, Sisi; Zhong, Nailiang; Guo, Qingke (Frontiers in Psychology, 2024)
Background: Despite growing recognition of dispositional mindfulness (DM) in psychological research, its cross-cultural mechanisms in promoting prosocial behavior remain unclear, particularly regarding the mediating role of different empathy dimensions. Purpose: This study investigated how DM influences prosocial behavior across cultural contexts, examining both the mediating effects of different empathy dimensions and the moderating role of cultural background in Chinese and Indonesian samples. Methods: Participants included 683 university students (357 Chinese, 326 Indonesian) who completed the Mindful Attention Awareness Scale (MAAS), Interpersonal Reactivity Index (IRI), and Self-Report Altruism Scale Distinguished by the Recipient (SRAS-DR). Mediation and moderation analyses were conducted using PROCESS macro. Results: Chinese participants demonstrated higher DM levels than Indonesian participants. In the Chinese sample, both perspective taking (PT) and empathic concern (EC) mediated DM's effects on prosocial behavior toward family (PBF), friends (PBFr), and strangers (PBS). However, in the Indonesian sample, PT and EC only mediated effects on PBFr. Cultural background significantly moderated DM's indirect effect on PBS through PT, with stronger effects in the Chinese sample. Fantasy and personal distress showed no significant mediating effects in either cultural context. Conclusion: This study reveals that DM enhances prosocial behavior through selective influence on different empathy dimensions, with cultural background moderating specific pathways. These findings extend our understanding of mindfulness's cross-cultural mechanisms and provide practical implications for culturally-adapted mindfulness interventions.